2021
DOI: 10.3390/rs13132551
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Landscape Patterns on Ecosystem Services Value: A Multiscale Buffer Gradient Analysis Approach

Abstract: In recent decades, substantial changes have occurred in the spatial structure and form of landscapes in metropolises; these have greatly impacted ecosystem provision capacities. Clarifying the impact mechanism of landscape patterns on ecosystem services can provide insights into regional ecological conservation and sustainable development measures. Although previous studies have explored the impacts of landscape patterns on ecosystem services at multiple scales, few studies have been conducted using the buffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 86 publications
1
30
0
Order By: Relevance
“…At present, the coupling response between landscape patterns and ecological processes has become point of concern in landscape ecology. From the research content perspective, some researchers have explored the correlation between habitat quality, ecosystem service value, and landscape patterns by analyzing their spatiotemporal changes [14,15]. For example, Yohannes, et al evaluated the response of hydrological ecosystem services to landscape changes and showed that soil and water conservation interventions are key to improving ecosystem services [16].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the coupling response between landscape patterns and ecological processes has become point of concern in landscape ecology. From the research content perspective, some researchers have explored the correlation between habitat quality, ecosystem service value, and landscape patterns by analyzing their spatiotemporal changes [14,15]. For example, Yohannes, et al evaluated the response of hydrological ecosystem services to landscape changes and showed that soil and water conservation interventions are key to improving ecosystem services [16].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, built-up land in densely populated areas expands under the influence of urban economic development, which eventually leads to the loss of ESV [ 25 ]. Furthermore, the expansion of built-up land has reduced the farmland area, thus reducing the supply capacity of ecosystem services and regional biodiversity [ 14 ]. In addition, we also found that wetland ecosystems had the highest ESVs, which increased continuously during 1980–2010 ( Table 6 and Table 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ecosystem service value (ESV) is the value of goods and services provided by ecosystems for human well-being, and is the main indicator for assessing ecosystem change. It quantifies the direct or indirect human benefits from ecosystem functions [ 14 , 15 ]. Currently, some studies (e.g., Cai et al [ 16 ] and Hu et al [ 17 ]) have demonstrated the relationship between urbanization and ESV, suggesting that urbanization indirectly leads to ESV changes by affecting the structure and function of natural ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…The MRYRUA is rich in natural resources, such as rivers and lakes, forest resources and cultivated land. The MRYRUA has an important strategic position in the national comprehensive transportation network, which includes railways of the Beijing-Kowloon and Beijing-Guangzhou trunk lines; the Shanghai-Kunming high-speed railway; the G55 Erenhot-Guangzhou expressway; several air routes and some river ports, basically forming a dense three-dimensional transportation network [55,56]. In 2019, the total GDP of the MRYRUA reached CNY 10,476.8 billion, accounting for 10.6% of China's GDP, and the total population reached 178.2 million, accounting for 12.7% of China's total population (http://www.stats.gov.cn (accessed on 18 July 2021)).…”
Section: Study Areamentioning
confidence: 99%